PENDIDIKAN KEWARGANEGARAAN (PKn) SEBAGAI WAHANA PENDIDIKAN DEMOKRASI DALAM MEWUJUDKAN SMART AND GOOD CITIZEN - Nastiti Mufidah (LP. Ma'arif Janggan Magetan, 2020)
Abstract: The purpose of this paper is to review democratic education which is then constructed in an analysis in which it is revealed about how citizenship education as a vehicle for democratic education in an effort to realize smart and good citizens. The writing of this article is a descriptive explanatory type of writing that explains the urgency of constructing the role of citizenship education as a vehicle for democratic education in realizing smart and good citizens. This writing uses the method of literature study which is a method that bases on various media as a source of literature relating to civic education, democratic education and various efforts in realizing smart and good citizens. The analysis based on the findings concludes that democratic education must become an integrated education with all aspects of citizens' lives in order to be able to build a political awareness of society holistically. Citizenship education with the principle of